Plasma soluble TIM-3 is increased in normoglycemic South Asian women compared to Nordic women after gestational diabetes mellitus and associated with markers of metaflammation - Helene Grannes; Archana Sharma; Anita Suntharalingam; Annika E. Michelsen; Pål Aukrust; Thor Ueland; Kåre I. Birkeland; Ida Gregersen; Sindre Lee-Ødegård; Bente Halvorsen (Heliyon, 2024)
Background: Women with South Asian ethnicity have a higher risk of developing type 2 diabetes mellitus (T2DM) compared with white women of European descent, especially after gestational diabetes mellitus (GDM). Central obesity and adipose tissue dysfunction have been linked to their higher risk of T2DM, but the mechanisms are not known. We hypothesize that low-grade, persistent immune cell activation is involved in metabolic disturbances following GDM with different influence according to ethnicity. Methods: We measured plasma levels of T cell exhaustion marker soluble T cell immunoglobin mucin domain 3 (sTIM-3), sCD25, sCD27 and soluble lymphocyte activation gene (sLAG)-3 in 266 women of South Asian (n = 160) and white Nordic (n = 106) ethnic background with a history of GDM. Results: Baseline plasma concentration of sTIM-3 was higher in South Asian women compared to Nordic women (p < 0.001). This difference was driven by higher sTIM-3 in South Asian women with NGT, compared to their Nordic counterparts (p = 0.005) but there were no significant differences comparing Nordic and South Asian women with altered glucose tolerance (AGT). Soluble TIM-3 correlated positively with waist-height ratio (WHtR) and body mass index across all groups, but whereas sTIM-3 correlated moderately and consistently with markers of metaflammation in South Asians, this pattern was not found in Nordic women. Mediation analysis indicated that 15 % of the difference found in adipose insulin resistance between ethnicities could be mediated by sTIM-3, and that 33 % of the difference in sTIM-3 concentrations could be mediated by WHtR. Moreover, T cell markers sCD27 and sLAG3 were also increased in South Asian women compared with Nordic women, further supporting involvement of T cell activation in these women. Conclusion: We found increased levels of sTIM-3, as well as additional markers of T cell activation/exhaustion, in a population of normoglycemic South Asian women with previous gestational diabetes as compared to women of Nordic descent. The possible causal relationship between T cell activation and metabolic dysfunction in high-risk South Asian women is however still elusive and merits further investigation.